2018
DOI: 10.1038/s41598-018-34250-9
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Par-1 kinase determine the localization of Bruchpilot at the Drosophila neuromuscular junction synapses

Abstract: Functional synaptic networks are compromised in many neurodevelopmental and neurodegenerative diseases. While the mechanisms of axonal transport and localization of synaptic vesicles and mitochondria are relatively well studied, little is known about the mechanisms that regulate the localization of proteins that localize to active zones. Recent finding suggests that mechanisms involved in transporting proteins destined to active zones are distinct from those that transport synaptic vesicles or mitochondria. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
(102 reference statements)
0
6
0
Order By: Relevance
“…Given the role of the cytoskeleton in AZ organization (Barber et al, 2018; Blunk et al, 2014; McNeill et al, 2020), STED was used to analyze the nanoscopic structure of Ib and Is AZs following disruption of several DEGs linked to cytoskeletal function. The Is-specific CG3085 protein encodes a Drosophila tektin of unknown function, although tektins are enriched in neurons and regulate microtubule stability in other species (Amos, 2008; Norrander et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Given the role of the cytoskeleton in AZ organization (Barber et al, 2018; Blunk et al, 2014; McNeill et al, 2020), STED was used to analyze the nanoscopic structure of Ib and Is AZs following disruption of several DEGs linked to cytoskeletal function. The Is-specific CG3085 protein encodes a Drosophila tektin of unknown function, although tektins are enriched in neurons and regulate microtubule stability in other species (Amos, 2008; Norrander et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Although there was no significant difference between average AZ number between controls and foxo mutants, we did observe more AZ's per bouton in the mutants. Previous studies have shown that accumulation of Brp in axons can limit active zone number at synaptic terminals (Barber et al, 2018 ). Foxo mutant larvae have been shown to have accumulations of Brp in the main axon (McLaughlin et al, 2016 ), but we were unable to capture this in the adult.…”
Section: Discussionmentioning
confidence: 98%
“…Although there was no significant difference between average AZ number between controls and foxo mutants, we did observe more AZ’s per bouton in the mutants. Previous studies have shown that accumulation of Brp in axons can limit active zone number at synaptic terminals (Barber et al 2018). Foxo mutant larvae have been shown to have accumulations of Brp in the main axon (McLaughlin et al 2016), but we were unable to capture this in the adult.…”
Section: Discussionmentioning
confidence: 99%